Improving Student Discipline in Reading the Qur'an Using an Interesting Tajwid Learning Method: Classroom Action Research at SD Negeri 101002 Simangambat - Hutasuhut, Tiurlan (Journal of Indonesian Primary School, 2024)
This study aims to improve students' discipline in reading the Qur'an using an interesting tajwid learning method. This study is a classroom action research that uses four steps, namely planning, action, observation and reflection. The subjects of this study were elementary school students. The data for this study were obtained using questionnaire and observation techniques. The questionnaire was used to measure student discipline and observation was used to analyze teacher and student learning activities. The data analysis technique used in this study was descriptive statistics by comparing the results obtained with indicators of research success. The results showed that an interesting tajwid learning method can improve student discipline. This can be seen from the increase in the percentage of student discipline in each cycle with details of the pre-cycle 51.61%, the first cycle 73.67% and in the second cycle it increased to 93.16%. Thus, the use of an interesting tajwid learning method can be used as an alternative to improve student discipline in reading the Qur'an.